HAKIKAT KETERAMPILAN BERBAHASA DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI - Chindytia; Goreti Rini Kristiantari, Maria; Ratna Lestari, Ni Kadek; Dinda Saraswati, Anak Agung; Mardiawan Saputra, I Putu Gede (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language skills are fundamental abilities required by every individual to communicate effectively in daily life. This article aims to examine the nature of language skills, which include listening, speaking, reading, and writing skills. The method used in this study is library research by reviewing various relevant scientific sources related to the topic. The results show that language skills play an important role in communication because they serve as the primary means of conveying ideas, thoughts, and information. These four skills are closely interconnected and cannot be separated in the communication process. Therefore, the development of language skills should be carried out in an integrated, systematic, and continuous manner to improve individual communication competence